Effects of captopril and losartan on lipid peroxidation, protein oxidation and nitric oxide release in diabetic rat kidney - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2003)
Increased oxidative stress has an important role in the pathogenesis of diabetic nephropathy. The aim of this study was to evaluate the effects of renin-anigiotensin system blockage, either by angiotensin-converting enzyme inhibition or angiotensin receptor blockage, on oxidative stress and nitric oxide release in diabetic rat kidneys. After induction of diabetes, six rats were given captopril, six rats were given losartan, and six rats served as diabetic controls. Six healthy rats were also included. At the end of an 8-week period nitric oxide release, lipid peroxidation and protein oxidation were measured in kidney cortices, and urinary albumin excretion (UAE) was determined in 24-h urine samples. Losartan- and captopril-treated diabetic rats had lower levels of UAE than diabetic controls. Diabetic rats had higher levels of lipid peroxidation and protein oxidation compared to healthy rats. NO release was significantly lower in diabetic groups than healthy controls. UAE levels showed a positive correlation with lipid peroxidation and a negative correlation with NO release. Inhibition of lipid peroxidation could be one of the protective mechanisms of renin-angiotensin axis inhibition in diabetic kidney tissues. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: nitric oxide; lipid peroxidation; ACE inhibition; AT1 receptor blockage; diabetic nephropathy; ANGIOTENSIN CONVERTASE INHIBITORS; ANTIOXIDANT ENZYMES; CARBONYL CONTENT; NEPHROPATHY; STRESS; DAMAGE; ENALAPRIL; MELLITUS; TISSUES; PLASMA